مسكن الأزمة وأثره على جودة الحياة الأسرية في الجزائر: السكن الجماعي أنموذجا - قاسمي، شوقي (جامعة باتنة 1 الحاج لخضر - كلية العلوم الإنسانية والاجتماعية, 2017)
مفهوم المسكن يمثل حدود الفراغ الذي يتشكل من جدران وسقف ويأوي إليه الإنسان بغية الراحة والطعام والمبيت. وتلبية الحاجات النفسية والاجتماعية والثقافية التي تكون مع الحاجات الجسدية تآلفا متكاملا يمتن العلاقة بين جسد الإنسان وإنسانيته. والتي من شأنها توفير متطلبات الراحة وتحقيق الإشباع النفسي، ضمان سلامة الصحة الجسمية لمستخدمي المسكن وقاطنيه من الأمراض والأوبئة التي قد تلحق بهم. إضافة إلى تزويد المسكن بالمياه الصالحة للشرب والاستعمال المنزلي، وتوفر شروط الوقاية من الحوادث المنزلية.
The concept of housing represents the boundaries of the space that is formed by walls and a roof and into which a person lives in order to rest and sleep. And satisfying the psychological, social and cultural needs. That, form an integrated harmony with the physical needs that strengthens the relationship between the human body and social. This would provide the requirements for comfort and achieve psychological satisfaction, ensure the safety and physical health in home users and residents from the diseases and epidemics. That may befall them. In addition to providing the dwelling with drinking water and household use, and providing conditions for the prevention of domestic accidents.
Keywords: علم النفس الاجتماعي -- أزمة السكن -- الصحة النفسية -- المشكلات الاجتماعية -- الجزائر